Effect of Silage Diet (Sweet Sorghum vs. Whole-Crop Corn) and Breed on Growth Performance, Carcass Traits, and Meat Quality of Lambs - Pu Wu (MDPI AG, 2021)
Diet and breed directly affect ruminant carcass traits and meat quality. Therefore, this research aimed to evaluate the effect of silage diet and breed on growth performance, carcass traits, and meat quality of lambs. A total of 28, 3–4 months old female lambs consisting of 14 Dorper lambs (DP) and 14 Thin-tailed Han lambs (TH) were allocated in a 2 × 2 factorial design and offered two experimental diets (sweet sorghum silage: SS; whole-crop corn silage: WS) for 90 days. Lambs fed the WS diet had a higher growth performance (p < 0.01), intramuscular fat content (p < 0.05), and bright meat color (p < 0.01) than lambs fed the SS diet. The lambs fed the SS diet showed a higher polyunsaturated fatty acid (PUFA) content than the lambs fed the WS diet (p < 0.01); there was no significant difference in growth performance and carcass characteristics between DP and TH lambs (p > 0.05). The meat of the DP lambs showed lower values of initial pH, shear force, lightness (L*), redness (a*), and saturated fatty acid (SFA) content (p < 0.05). The lamb breed influenced fewer variables of growth performance and carcass characteristics compared to the diet. The lambs fed the SS diet had higher nutritional quality meat than lambs fed the WS diet.